Nothing but trouble a Kevin Kerney novel - McGarrity, Michael (New York, N.Y. : Dutton, 2005)
Reluctantly working as a technical adviser for a western being filmed in New Mexico, Santa Fe police chief Kevin Kerney finds the murdered body of a young man near an isolated Mexican border crossing and discovers that a large-scale drug-smuggling operation may be responsible
86978
Keywords: Kerney, Kevin (Fictitious character) -- Fiction; Police -- New Mexico -- Santa Fe -- Fiction; Police chiefs -- Fiction; Santa Fe (N.M.) -- Fiction; Mystery fiction